Efficacy of Infection Eradication in Antibiotic Cement-Coated Intramedullary Nails for Fracture-Related Infections, Nonunions, and Fusions - Janet D. Conway; Ahmed H. Elhessy; Selin Galiboglu; Nirav Patel; Martin G. Gesheff (MDPI AG, 2022)
Antibiotic cement-coated intramedullary nails (ACCINs) are increasing in popularity as a viable solution for the treatment of fracture-related infections (FRIs), infected long bone nonunions, and arthrodeses without an external fixator. ACCINs effectively manage to fulfill three of the basic principles for eradicating osteomyelitis: dead space management, antibiotic delivery, and bone stability. We performed a retrospective review of 111 patients who were treated with ACCINs between January 2014 and December 2020. In our series, 87.4% (n = 97) of patients achieved healed and uninfected bone or stable arthrodesis at a mean follow-up of 29.2 months (range, 6-93 months). Additionally, 69.1% (n = 67) of healed patients were resolved after only one procedure, and the remainder (30.9%, n = 30) healed after one or more additional procedures. The mean number of additional procedures was 2.1 (range, 1-6 additional procedures). The overall limb salvage rate was 93.7% (n = 104). The majority of the total cohort were successfully treated in only one surgery. This study suggests that ACCINs are effective in the treatment of FRIs, infected long bone nonunions, and infected ankle and knee arthrodeses.